Disabling practices - Trescher, Hendrik (Cogent social sciences, 2017)
Following Foucault’s theory of discourse this article aims at reformulating the established concept of disability. To this end, the author reconstructs ways in which disabling practices of subjectivation occur in and through public media discourses. The article focuses on the discoursive production of infantile identities in people with cognitive disabilities. The examples demonstrate that this discoursive production occurs in self-representational media formats and in outside media representations. Hence, the author develops a concept of disability as a discoursively produced ordering category, from which follows a reformulation of the disability concept. This reformulated concept, which grasps disability as discourse disability, allows in turn for a perspective on disability as practice and thus as independent from the subject. To conclude, the article discusses implications of such a perspective of disability for pedagogy and the social sciences, ultimately arguing for a broader definition of disability and for making respective benefits a matter of social pedagogy.